Agricultural automation : (CRC Press, Taylor & Francis Group, 2013)
Agricultural automation is the core technology for computer-aided agricultural production management and implementation. An integration of equipment, infotronics, and precision farming technologies, it creates viable solutions for challenges facing the food, fiber, feed, and fuel needs of the human race now and into the future. Agricultural Automation: Fundamentals and Practices provides a comprehensive introduction of automation technologies for agriculture.